2004
DOI: 10.1002/pon.865
|View full text |Cite
|
Sign up to set email alerts
|

Anticipating loss and other temporal stressors predict traumatic stress symptoms among partners of metastatic/recurrent breast cancer patients

Abstract: This study examined pre- and post-loss levels of posttraumatic stress symptoms (intrusion and avoidance) in partners of metastatic/recurrent breast cancer patients, and the relationship of these symptoms to past, current, and anticipatory stressors. The results indicate that 34% (17/50) of the partners experienced clinically significant symptom levels prior to the patients' deaths. Prior to loss, partners' symptoms were positively associated with their current level of perceived stress and anticipated impact o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
24
0
5

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(32 citation statements)
references
References 33 publications
3
24
0
5
Order By: Relevance
“…There are existing measures of anticipatory grief (Butler et al, 2005;Mystakidou et al, 2005) and grief (Hogan et al, 2001;Prigerson et al, 1997) primarily from the "death of a loved one" literature that could be adapted to the business failure context. The period of business failure delay could be measured as the number of days after the business reaches a threshold specified by bankruptcy prediction models.…”
Section: Discussionmentioning
confidence: 99%
“…There are existing measures of anticipatory grief (Butler et al, 2005;Mystakidou et al, 2005) and grief (Hogan et al, 2001;Prigerson et al, 1997) primarily from the "death of a loved one" literature that could be adapted to the business failure context. The period of business failure delay could be measured as the number of days after the business reaches a threshold specified by bankruptcy prediction models.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been shown that the degree to which the attitudinal and behavioral changes take place depends on the stage of cancer (Butler et al, 2005;Braun et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Estudo recente encontrou altos níveis de ansiedade em cuidadores primários de pacientes do sexo masculino (45%), como também em cuidadores de pacientes do sexo feminino (47% ) 9 . A depressão é mais estudada e descrita em cerca de 30% dos cuidadores, sendo mais prevalente em cuidadores de pacientes do sexo feminino [9][10][11][12] . Verifica-se também aumento progressivo desses sintomas conforme a aproximação do óbito 6 .…”
Section: Introductionunclassified